Caracterização fotossintética da espécie isohídrica pata-de-elefante em condições de deficiência hídrica - Bertolli, Suzana Chiari [UNESP]; De Souza, Juliano; Souza, Gustavo Maia (My University, 2015)
The maintenance of a plant water status is essential for keeping of its development in environ-ments with limited water availability. Different species have different mechanisms that provide greater ability to survive under drought conditions. The objective of this study was to evaluate physiological parameters changes of the isohydric species Beaucarnea recurvate Lem. under irrigation suspension. The study involved experiments with slow dehydration (SD) performed by withholding water followed by plants rehydration, and with rapid dehydration (RD), where individual leaves were detached and placed to dehydrate in the laboratory bench. The results showed that although of the soil water content (% H2O) reach critical values (12%) in the first days of the irrigation suspension, the plants showed maintenance of the relative water content (≅80%) over the 54-day SD period, when the net photosynthesis (PN) reached null values. Throughout SD, it was ob-served that the PN, stomatal conductance (gs), instantaneous carboxylation efficiency, the electrons transport rate, the potential quantum efficiency of PSII and chlorophyll content were reduced. In RD, experiment was observed a high correlation between PN and gs. The results suggest that the reduction in photosynthesis was initially caused by a stomatal adjustment that culminated in an imbalance between photochemical energy production and its consumption by biochemical apparatus of photosynthesis. However, after rehydration, all gas exchange parameters were recovered, indicating that the isohydric behavior of this species contributed to the plants did not suffer extensive damage during a prolonged period of irrigation suspension.
Photosynthetic characterization of the isohidric species ponytail palm under water deficit
Keywords: Beaucarnea recurvata Lem.; Dehydration; Gas exchange; Water regulation